2018
DOI: 10.1128/jb.00002-18
|View full text |Cite
|
Sign up to set email alerts
|

Photobacterium damselae subsp. damselae, a Generalist Pathogen with Unique Virulence Factors and High Genetic Diversity

Abstract: subsp. causes vibriosis in a variety of marine animals, including fish species of importance in aquaculture. It also may cause wound infections in humans that can progress into a fatal outcome. Two major virulence factors are encoded within the large conjugative plasmid pPHDD1: the phospholipase-D damselysin (Dly) and the pore-forming toxin Phobalysin P (PhlyP). The two toxins exert hemolytic and cytolytic activity in a synergistic manner. Albeit PhlyP has close homologues in many species, it has unique featur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 36 publications
(44 citation statements)
references
References 51 publications
1
43
0
Order By: Relevance
“…damselae can produce a number of virulence factors to cause pathogenicity in hosts. The four main virulence factors recognized so far have cytotoxic activity for different cell types ( Osorio et al, 2018 ). Here, we found that the 31 rainbow trout strains could be divided into four distinct categories according to their haloes of β-hemolysis on sheep blood agar: a large β-hemolytic halo (LH) (7 strains), a medium halo (MH) (6 strains), a small halo (SH) (15 strains) or virtually absence of β-hemolytic halo (NH) (3 strains) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…damselae can produce a number of virulence factors to cause pathogenicity in hosts. The four main virulence factors recognized so far have cytotoxic activity for different cell types ( Osorio et al, 2018 ). Here, we found that the 31 rainbow trout strains could be divided into four distinct categories according to their haloes of β-hemolysis on sheep blood agar: a large β-hemolytic halo (LH) (7 strains), a medium halo (MH) (6 strains), a small halo (SH) (15 strains) or virtually absence of β-hemolytic halo (NH) (3 strains) ( Figure 2 ).…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies have analyzed a reduced number of strains, and reported as many as 7 O-serogroups among 16 strains analyzed ( Fouz et al, 1992 ). A recent comparative analysis conducted with virulent strains of this pathogen, revealed that strains of different serogroups contain distinct gene repertories within a putative cluster for cell envelope polysaccharide synthesis ( Osorio et al, 2018 ). We therefore searched the polysaccharide synthesis homologous clusters within the genomes of strains DK2, DK3, DK20, and DK29.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations